Drug-coated balloons in the European Registry of Chronic Total Occlusion: the ERCTO registry - Ciardetti, Niccolò; Mattesini, Alessio; Werner, Gerald S.; Atmowihardjo, Iskandar; Zaczkiewicz, Myron; Bas, Schölzel; Ayoub, Mohamed; Ladwiniec, Andrew; Weber-Albers, Joachim; Lauer, Bernward; Kovacic, Mihajlo; Prog, Rostislav; et al. (JACC Cardiovascular interventions, 2025)
Background - Drug-coated balloons (DCBs) are increasingly used in percutaneous coronary intervention (PCI). Their application for chronic total occlusions (CTOs) is a promising option to limit stent length in diffuse disease and avoid stent underexpansion and malapposition in negatively remodeled distal vessel segments. - Objectives - The aim of this study was to analyze CTO PCI procedures recorded in ERCTO (European Registry of Chronic Total Occlusion) to investigate frequency of use, patient and lesion characteristics, and in-hospital outcomes of DCBs. - Methods - CTO cases entered into the database from 2016 to 2023 were examined and categorized according to DCB use. DCB-treated patients were further divided into 2 groups: DCBs only and DCBs in association with drug-eluting stents. To minimize the potential impact of confounding factors, 1:1 propensity score matching was applied. - Results - Of 40,449 CTO PCIs performed at 184 centers, DCBs were used in 2,506 (6.2%), increasing from 3.4% (n = 185 of 5,498) in 2016 to 14.9% (n = 705 of 4,722) in 2023. In-hospital complications were infrequent, but DCB-treated CTOs had significantly lower rates of pericardial tamponade (0.1% [n = 2 of 2,506] vs 0.4% [n = 169 of 37,943]; P = 0.006). After propensity score matching, DCB use led to reduced drug-eluting stent length (44.2 ± 36.9 mm [95% CI: 42.7-45.7 mm] vs 58.1 ± 35.9 mm [95% CI: 56.7-59.5] mm; P < 0.001). Contrast volume was lower in the DCB-treated patients (202.4 ± 109.8 mL [95% CI: 198.1-206.7 mL] vs 211.6 ± 123 mL [95% CI: 206.8-216.4 mL]; P = 0.005). - Conclusions - The use of DCBs in CTO recanalization is increasing and is associated with a reduction in the length of stents implanted, as well as a decrease in contrast volume and a lower rate of pericardial tamponade.